High-mobility group AT-hook protein 2 expression and its prognostic significance in MGMT methylated and unmethylated glioblastoma - Schwarm, Frank; Uhle, Florian; Schänzer, Anne; Acker, Till; Stein, Marco; Reinges, Marcus H. T.; Weischer, Cornelia; Weigand, Markus A.; Uhl, Eberhard; Kolodziej, Malgorzata A. (International journal of oncology, 2016)
High-mobility group AT-hook protein 2 (HMGA 2) is a transcription factor associated with malignancy and poor prognosis in a variety of human cancers. We correlated HMGA 2 expression with clinical parameters, survival, and O-6-methylguanine-DNA methyltransferase methylation status (MGMT) in glioblastoma patients.